Перша міжнародна наукова конференція на тему “Нетрадиційні, нові і забуті види рослин: наукові та практичні аспекти культивування” - Klymenko, S.V.; Brindza, J.; Grygorieva, O.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2015)
It is presented information about First International scientific conference "Non-traditional, new and forgotten plant species: scientific and practical aspects of cultivation", which is taken place in Kyiv 10–12 september 2013. In conference are participated more than 100 people from 17 countries (Ukraine, Azerbaijan, Armenia, Belarus, Bulgaria, Georgia, Kazakhstan, Latvia, Lithuania, Moldova, Poland, Russia, Serbia, Slovakia, Uzbekistan, France, Czech Republic) – representatives of botanical and medical research institutes and universities, botanical gardens, arboretums and agricultural experienced stations. The reports are elucidated of the results of studies of less common fruit, vegetable, medicinal, forage, technical and ornamental plants. It was shown that implementation commodity production will increase the diversity of products and enlarge of export potential. Growing plants with high content of bioactive substances will improve the quality and nutritional value of products for the recovery of population health.